Family members' perception of their needs in critical care units at a tertiary hospital in Malawi: A qualitative study - Angellina Mankhamba Kalolo; Chimwemwe Mula; Rodwell Gundo (BMC, 2023)
Abstract Background Family members experience an emotional crisis when their loved one is critically ill and admitted to a critical care unit (CCU). An extensive literature has explored optimal ways to interact with families in the critical care setting, including intervention studies. What is less explored are perceptions of family members in low-income settings including Malawi. In such settings, perceptions may differ as a consequence of different cultural practices and resource limitations (personnel and technology). Therefore, this study explored family members' perceptions of their needs in CCUs at a tertiary hospital in Malawi. Study designs and methods The study used a qualitative descriptive design. Data were gathered through interviews with 12 participants who were purposively selected from immediate family members of patients hospitalized for 48 h or more in adult intensive care unit (ICU) and high dependency unit (HDU). The interviews were audio recorded and transcribed verbatim. Data analysis followed the steps of content analysis. Findings The following four themes were identified: perceived information, physical, and psychosocial needs, and coping mechanisms of the family members. The family members needed information about their patient's progress frequently and viewed this as a priority compared to other needs such as comfort and food. Conclusion This study suggests that there should be a collaborative relationship between the CCU team and family members in order to meet their needs. Findings affirm the need for health professionals to develop guidelines or standards that promote frequent discussions with CCU family members as a means to provide support and lessen anxiety.